Workforce Planning in the Intelligence Community A Retrospective - Nemfakos, Charles (RAND Corporation, 2013)
This report chronicles intelligence community efforts over more than half a decade to improve community-wide workforce planning and management. As decisionmakers look ahead to an era of constrained budgets, they must avoid repeating earlier workforce planning mistakes because the consequences of such mistakes can be long lasting. The tools described will help decisionmakers maintain workforce capabilities as budgets decline.